Developmental toxicity and neurotoxicity of synthetic organic insecticides in zebrafish (Danio rerio): A comparative study of deltamethrin, acephate, and thiamethoxam. (May 2018) - Liu, XingYu; Zhang, QiuPing; Li, ShiBao; Mi, Ping; Chen, DongYan; Zhao, Xin; Feng, XiZeng
Abstract: Synthetic organic insecticides, including pyrethroids, organophosphates, neonicotinoids and other types, have the potential to alter the ecosystems and many are harmful to humans. This study examines the developmental toxicity and neurotoxicity of three synthetic organic insecticides, including deltamethrin (DM), acephate (AP), and thiamethoxam (TM), using embryo-larval stages of zebrafish ( Danio rerio ). Results showed that DM exposure led to embryo development delay and a significant increase in embryo mortality at 24 and 48 h post-fertilization (hpf). DM and AP decreased embryo chorion surface tension at 24 hpf, along with the increase in hatching rate at 72 hpf. Moreover, DM caused ntl, shh, and krox20 misexpression in a dose-dependent manner with morphological deformities of shorter body length, smaller eyes, and larger head-body angles at 10 μg/L. TM did not show significant developmental toxicity. Furthermore, results of larval rest/wake assay indicated that DM (>0.1 μg/L) and AP (0.1 mg/L) increased activity behavior with different patterns. Interestingly, as an insect-specific pesticide, TM still could alter locomotor activity in zebrafish larvae at concentrations as low as 0.1 mg/L. Our results indicate that different types of synthetic organic insecticides could create different toxicity outcomes in zebrafish embryos and larvae. Graphical abstract: Image 1 Highlights: Deltamethrin and acephate can induce zebrafish developmental delay and malformation. Deltamethrin and acephate can decrease embryonic surface tension. Deltamethrin, acephate, thiamethoxam induce larval locomotor activity increase. Embryonic exposure to deltamethrin or acephate damages CaP axons.